anonymous
  • anonymous
The sides of a triangle are x, x+1, 2x-1 and its area is x root 10 .What is the value of x?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
So if the sides = x>-2 Then the area would be that ^10 right?
anonymous
  • anonymous
cn u xplain??
RadEn
  • RadEn
Heron's formula is work area = sqrt(s(s-a)(s-b)(s-c)) with s = (perimeter of triangle)/2 a,b,c are the sides triangle

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

RadEn
  • RadEn
first, determine the perimeter of that triangle perimeter = a + b + c = x + x+1 + 2x - 1 = 4x so, s = perimeter/2 = 4x/2 = 2x
RadEn
  • RadEn
now, use the Heron's formula above area = sqrt(s(s-a)(s-b)(s-c)) known area of that triangle is xsqrt(10), so we have the equation sqrt(s(s-a)(s-b)(s-c)) = x sqrt(10)
RadEn
  • RadEn
distribute the values of s = 2x, a = x, b = x+1, and c = 2x -1 into equation above : sqrt(s(s-a)(s-b)(s-c)) = x sqrt(10) sqrt(2x(2x- x)(2x - (x+1))(2x - (2x-1)) = x sqrt(10) simplify, we get sqrt(2x * x * (x-1) * 1) = x sqrt(10) sqrt(x^2 * 2(x-1)) = x sqrt(10) sqrt(x^2) * sqrt(2(x-1)) = x sqrt(10) x sqrt(2(x-1)) = x sqrt(10)
RadEn
  • RadEn
just take identicaly, the value in radical must be same. so 2(x-1) = 10 divided by 2 on both sides, we get x-1 = 10/2 x-1 = 5 add by 1 to both sides, get x = 5 + 1 = 6
RadEn
  • RadEn
does that make sense, @juhaINA ?
anonymous
  • anonymous
yah..!!:)
RadEn
  • RadEn
ok, glad can help you :)
anonymous
  • anonymous
i hv a question.
RadEn
  • RadEn
what is that ?
anonymous
  • anonymous
in d formula:s-a,s-b,s-c.v don hv to do dat in this question?
RadEn
  • RadEn
well it is already be clear for you, right. this site might useful :) http://www.mathsisfun.com/geometry/herons-formula.html
anonymous
  • anonymous
k..thnx
RadEn
  • RadEn
you're welcome

Looking for something else?

Not the answer you are looking for? Search for more explanations.